2014
DOI: 10.3389/fpsyt.2014.00054
|View full text |Cite
|
Sign up to set email alerts
|

Gone to Pot – A Review of the Association between Cannabis and Psychosis

Abstract: Cannabis is the most commonly used illicit drug worldwide, with ~5 million daily users worldwide. Emerging evidence supports a number of associations between cannabis and psychosis/psychotic disorders, including schizophrenia. These associations-based on case-studies, surveys, epidemiological studies, and experimental studies indicate that cannabinoids can produce acute, transient effects; acute, persistent effects; and delayed, persistent effects that recapitulate the psychopathology and psychophysiology seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
225
0
14

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(245 citation statements)
references
References 262 publications
(402 reference statements)
6
225
0
14
Order By: Relevance
“…An analysis of results from 35 studies revealed a pooled odds ratio of 1.4 for risk of developing psychosis in individuals with any history of cannabis exposure and an odds ratio of 2.1 among individuals with histories of more frequent use [7]. In addition, a relationship between the age of initiation of cannabis use and age of onset of psychosis has also been well documented, with most studies finding that cannabis use precedes onset of psychosis and that the amount of cannabis exposure in adolescence may be the strongest determinant of this association [4]. However, several issues have complicated interpretation of these findings, including the role of comorbid substance use, of male sex (which is associated with higher rates of cannabis use and earlier age of onset of schizophrenia), of lower socioeconomic status, and of the potentially poor reliability of self-reported histories of past cannabis use.…”
Section: Cannabis and Schizophreniamentioning
confidence: 99%
See 3 more Smart Citations
“…An analysis of results from 35 studies revealed a pooled odds ratio of 1.4 for risk of developing psychosis in individuals with any history of cannabis exposure and an odds ratio of 2.1 among individuals with histories of more frequent use [7]. In addition, a relationship between the age of initiation of cannabis use and age of onset of psychosis has also been well documented, with most studies finding that cannabis use precedes onset of psychosis and that the amount of cannabis exposure in adolescence may be the strongest determinant of this association [4]. However, several issues have complicated interpretation of these findings, including the role of comorbid substance use, of male sex (which is associated with higher rates of cannabis use and earlier age of onset of schizophrenia), of lower socioeconomic status, and of the potentially poor reliability of self-reported histories of past cannabis use.…”
Section: Cannabis and Schizophreniamentioning
confidence: 99%
“…Arguing in support of a causal relationship is the consistently replicated evidence in different populations that cannabis use precedes psychotic symptoms [20,21], there is a dose effect [16], and there are coherent, plausible biological mechanisms [4,22,23].…”
Section: Cannabis and Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand evidence shows that the increase in cannabis consumption is proportionate to the increase in the proportion of people seeking treatment for psychotic disorders [1]. While there is some evidence that consuming cannabis is a risk factor for several types of psychotic disorders [2], the link between these two factors needs to be better quantified. These days, researchers attempted to understand whether specific patterns of cannabis use such as potency or age are associated with a higher risk of developing psychotic disorders.…”
Section: Introductionmentioning
confidence: 99%